THE PERMANENT DETECTION OF SHIFTS IN THE PROBLEM OF CALCULATION AUTOMATION OF THE CORRECTION RAIL CURVES - Lahuta, V. V. (Science and Transport Progress, 2008)
The numerical method of solution of a differential equation of railway shifts is presented allowing to calculate the quantity of shifts in any point of a railway curve during its straightening. Shifts calculated between the points of measurement of bend arrows can be used as control ones.